Genetic polymorphisms of IGF1, GH, and OPN genes in crosses Peranakan Ongole cattle based on birth type in Central Java - Anneke Anggraeni; Chalid Talib; Santi Ananda Asmarasari; Tati Herawati; Erik Andreas (Indonesian Center for Animal Research and Development (ICARD), 2017)
Genetic Polymorphisms of IGF1, GH, and OPN Genes in Crossbred of Peranakan Ongole Cattle Based on Birth Type in Central Java. Improved productivity by crossing Peranakan Ongole (PO) cattle to exotic beef cattle through AI mating is preferred by many farmers in Central Java. Fertility determines the ability of a cow to give birth. IGF1 gene is predicted to affect either twin or multiple births in cattle, whereas GH and OPN genes determine reproductive fertility. Genetic polymorphisms of these three genes were studied in the crossbred of PO cattle for single birth (S) as well as twin and multiple (M) births or their historical (M) ones from two districts in Central Java, from Sragen (S = 7 hd and M = 13 hd.) and from Kendal (S = 9 hd, and M = 16 hd.). Genetic polymorphisms were identified by PCR-RFLP (polymerase chain reaction - restriction fragment length polymorphism) method using restriction enzymes of SnaBI (IGF1 gene), MSpI (GH gene), and BsrI (OPN gene). IGF1|SnaBI locus in the observed crossbred PO did not have SNP polymorphism or monomorphic for single and twins or multiple births. In contrast, GH|MSpI and OPN|BsrI loci were polymorphic with quite a high degree of diversity. In conclusion, the IGF1|SnaBI locus cannot be used to investigate possible genetic control of twins and multiple births, whilst GH|MSpI and OPN|BsrI polymorphisms can be considered as initial information for selection on fertility traits in beef cattle.